Genome sequence and description of Actinomyces polynesiensis str. MS2 sp. nov. isolated from the human gut. (July 2016) - Cimmino, T.; Metidji, S.; Labas, N.; Le Page, S.; Musso, D.; Raoult, D.; Rolain, J.-M.
Abstract: Actinomyces polynesiensis strain MS2 gen. nov., sp. nov. is a newly proposed genus within the family Actinomycetaceae, isolated from the stools of a healthy individual in Raiatea Island (French Polynesia, South Pacific). Actinomyces massiliensis is an anaerobic, Gram-positive organism. Here we describe the features of this organism, together with the complete genome sequence and annotation—2 943 271 bp with a 70.80% G+C content, assembled into 15 scaffolds and containing 2080 genes.